E-menu for food orders in the hotel rooms - Ryabenka, Anastasia; Drokina, Nina (My University, 2015)
E-menu is a system of orders, allowing the visitor to get acquainted with the assortment, which is offered by the department of «Food and Beverage» using your tablet or mobile application without the help of the waiter.
Keywords: food; hotel rooms; hospitality; готельні номери; харчування; готельний бізнес; гостиничный бизнес; гостиничные номера; питание; кафедра туристичного та готельного бізнесу